2014
DOI: 10.1007/s00271-014-0446-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of nutsedge (Cyperus esculentus L. var sativus Boeck.) tuber production to drip irrigation based on volumetric soil water content

Abstract: Cultivated nutsedge is a common crop in Valencia (Spain). The aim of this research, which was conducted over two consecutive years, was to compare the productive response of the nutsedge crop with drip irrigation and traditional furrow irrigation, calculating the yield and the irrigation water use efficiency (IWUE). The volumetric soil water content was monitored with capacitance probes. Four irrigation strategies were considered: three in drip irrigation [D70, D80, and D90 with refill points at 70%, 80%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
2
5
1
1
Order By: Relevance
“…In 2011, rains occurred primarily in spring (Figure 1 Regarding the percentage of I applied in relation to the seasonal ETo -Effective rainfall, these values represent 51.7% and 51.2%, respectively, for 2011 and 2013. These values are lower than those that were obtained in previous studies, both in ridges (on average 93.8%; Pascual-Seva et al, 2015) and in flat raised beds (on average 141.8%; Pascual-Seva et al, 2014) in which the management was automated, with each event being started when the VSWC at a 0.10-m depth in ridges reached 85% of the FC value and stopped when the sum of the VSWC values at 0.10-m, 0.20-m and 0.30-m depths in ridges reached the corresponding FC value. The percentages that were obtained in this study show a better adjustment of the I applied to water requirements (considered better adjusted to the water retention capacity of the soil in the root zone) than in the previous studies.…”
Section: Irrigation Managementcontrasting
confidence: 76%
See 2 more Smart Citations
“…In 2011, rains occurred primarily in spring (Figure 1 Regarding the percentage of I applied in relation to the seasonal ETo -Effective rainfall, these values represent 51.7% and 51.2%, respectively, for 2011 and 2013. These values are lower than those that were obtained in previous studies, both in ridges (on average 93.8%; Pascual-Seva et al, 2015) and in flat raised beds (on average 141.8%; Pascual-Seva et al, 2014) in which the management was automated, with each event being started when the VSWC at a 0.10-m depth in ridges reached 85% of the FC value and stopped when the sum of the VSWC values at 0.10-m, 0.20-m and 0.30-m depths in ridges reached the corresponding FC value. The percentages that were obtained in this study show a better adjustment of the I applied to water requirements (considered better adjusted to the water retention capacity of the soil in the root zone) than in the previous studies.…”
Section: Irrigation Managementcontrasting
confidence: 76%
“…When properly designed, installed and managed, drip irrigation systems usually result in high uniformities and application efficiencies (Evans et al, 2007); furthermore, the wetted area is smaller, as water is localised near the plant, thus decreasing soil evaporation in the early stages of the plant (Allen et al, 1998) and conserving water compared to other irrigation methods. The first studies of this irrigation method performed in chufa demonstrated that it could be an alternative to the traditional irrigation (Pascual-Seva et al, 2015). Different refill points (soil moisture levels before the start of each irrigation event) in ridges were compared; the two drip irrigation refill points that maintained higher levels of soil moisture [80% and 90% of field capacity (FC)] resulted in a higher yield (2.40 kg m -2 and 2.80 kg m -2 , respectively) than the traditional furrow irrigation (2.14 kg m -2 ) and resulted in a higher IWUE (4.22 kg m -3 on average for drip irrigation; 2.09 kg m -3 for furrow irrigation; Pascual-Seva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the profitability of the RDI, as presented in Pascual-Seva et al [49], under the conditions of this study can help to make decisions that reduce water consumption. The gross revenue and water economic value were determined, taking into account the MY and the IWUE obtained in this study, as well as the average price of the onion bulbs over the previous three years (0.21 € kg −1 [50].…”
Section: Crop Profitabilitymentioning
confidence: 99%
“…Del análisis de esta interacción se deduce que únicamente existieron diferencias entre los pesos unitarios de las dos estrategias, a favor de H2 en 2007 y 2008. Los valores de obtenidos en este estudio son similares a los obtenidos en riego localizado (Pascual-Seva et al, 2015). La eficiencia en el uso del agua de riego (EUAR) no se vio afectada por la estrategia de riego, pero sí por el año de experimentación (p ≤ 0.01), obteniéndose los valores mínimos (1.77 kg·m Con el programa WinSRFR 3.1 se consiguió una adecuada modelización de los riegos, obteniendo los respectivos valores de eficiencia de aplicación y uniformidad de distribución.…”
Section: 4-diseño Experimental Y Análisis Estadísticounclassified